2015
DOI: 10.1038/ejcn.2015.93
|View full text |Cite
|
Sign up to set email alerts
|

Early life determinants of dietary patterns in preschool children: Rhea mother–child cohort, Crete, Greece

Abstract: The results from this analysis indicate the important role of socio-demographic factors on children's dietary preferences in early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Other studies targeting preschoolers have also identified maternal education as a significant determinant of dietary patterns in children of this age group [20,35]. Lower education amongst mothers predicted higher adherence to the "Processed and Fast Food" dietary pattern amongst French preschoolers and to the "Snacky" pattern amongst Greek under five children [20,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies targeting preschoolers have also identified maternal education as a significant determinant of dietary patterns in children of this age group [20,35]. Lower education amongst mothers predicted higher adherence to the "Processed and Fast Food" dietary pattern amongst French preschoolers and to the "Snacky" pattern amongst Greek under five children [20,35].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, dietary pattern analysis was proposed as a holistic approach that investigates the joint effects of multiple dietary components on obesity risk [16,17]. Few studies have examined dietary patterns amongst preschoolers and their association with the risk of overweight or obesity [18][19][20][21][22]. A dietary pattern rich in French fries and sweetened beverages and low in dairy products and water was found to be associated with increased risk of overweight and obesity amongst 3-6-year-old French children [18].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, principal component analysis (PCA) is a multidimensional reduction analysis method to examine the correlations of food intakes, and is commonly used in nutritional epidemiology [ 13 ]. Several studies using PCA reported several dietary patterns in children and adolescents as “healthy”, “traditional”, “Western”, and “junk or processed food intakes”, among others [ 5 , 14 , 15 ]. However, Hu suggested that much more research is necessary in diverse populations due to sociocultural differences [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three dietary patterns were determined with the use of PCA: the 'Mediterranean', 'Snacky' and 'Western' dietary patterns (20) . The online Supplementary Table S1 describes the foods included in each pattern and their factor loadings.…”
Section: Dietary Assessmentmentioning
confidence: 99%